Experimental tests of surface‐enhanced Raman scattering: Moving beyond the electromagnetic enhancement theory. (28th October 2020) - Heeg, Sebastian; Mueller, Niclas S.; Wasserroth, Sören; Kusch, Patryk; Reich, Stephanie
Abstract: The electromagnetic enhancement theory describes surface‐enhanced Raman scattering (SERS) as a Raman effect that takes place in the near‐field of a plasmonic nanostructure. The theory has been very successful in explaining the fundamental properties of SERS, modelling the performance of different metals as enhancing materials and optimizing SERS hotspots for strongest possible enhancement. Over the last decade, a number of carefully designed experimental studies have examined predictions of the electromagnetic theory like the size and shape of SERS hotspots, the absolute magnitude of the enhancement and the width of the SERS resonance. Although the overall picture was quite satisfactory, the theory failed to predict key aspects of SERS, for example, the absolute magnitude of the plasmonic enhancement. We scrutinize these experiments and review them focusing on the results that require going beyond the electromagnetic enhancement theory. We argue that the results of these experiments create the need to develop the theory of SERS further, especially the exact role of plasmonic enhancement in inelastic light scattering. Abstract : This critical review shows that the electromagnetic enhancement theory, which successfully describes the fundamental properties of surface‐enhanced Raman scattering, fails to predict key aspects like the absolute magnitude and the energy window of plasmonic enhancement. We would like to start a discussion within the scientific community how to further develop the theoretical description of surface‐enhanced Raman scattering.